Spectrum allocation and power control for D2D communication underlay 5G cellular networks. (28th September 2021) - Benbraika, Mohamed Kamel; Bitam, Salim
The fifth-generation (5G) of cellular networks promises to assure low latency and high data rate. Device-to-device (D2D) communication technology can achieve those goals since it improves throughput and expands cell radius. However, the limited spectrum and battery life of devices are considered as a handicap for efficient D2D communication. The joint spectrum allocation and power control problem is a nonlinear and controlled by many nonlinear constraints. To deal with this issue, we propose in this paper, a new bio-inspired approach called enhanced bee life algorithm for D2D communications (E-BLAD2D). This proposal generates an initial population according to the simulated annealing algorithm, then, an enhanced bee life algorithm is suggested to improve the expected solution. After a set of simulations, the results obtained showed that E-BLAD2D surpasses genetic algorithm and particle swarm optimisation in terms of network throughput and the convergence speed to reach the optimal solution with a reduced computational complexity.